Mechanism of miR‐424‐5p promoter methylation in promoting epithelial–mesenchymal transition of hepatocellular carcinoma cells. Issue 4 (20th January 2022) - Lv, Hong‐Cheng; Lv, Yan‐Yan; Wang, Gang; Zhang, Xie‐Hua; Li, Sheng‐Nan; Yue, Xiao‐Fen; Lu, Wei
Abstract: The current study set out to clarify the role of miR‐424‐5p promoter methylation in epithelial mesenchymal transition (EMT) of hepatocellular carcinoma (HCC) cells. The findings of quantitative real‐time‐polymerase chain reaction and methylation‐sensitive high‐resolution melting assays elicited that miR‐424‐5p was poorly expressed in HCC tissues and cells while highly methylated. Meanwhile, upon demethylation, miR‐424‐5p expression levels were partly recovered in HCC cells. In addition, miR‐424‐5p upregulation reduced cell viability and elevated apoptosis of HCC cells, in parallel with increased N‐cadherin and decreased E‐cadherin levels. Dual‐luciferase reporter assay further validated that miR‐424‐5p bound to the kinesin family member 2A (KIF2A), and miR‐424‐5p overexpression downregulated KIF2A. In addition, KIF2A overexpression reversed the miR‐424‐5p‐driven changes in terms of cell viability, apoptosis and EMT‐related protein levels. Furthermore, xenograft tumors were established via injection of Huh7 cells, followed by miR‐424‐5p overexpression in vivo, which inhabited KIF2A downregulation and attenuated tumor growth along with decreased Ki67 positive expression, diminished N‐cadherin and elevated E‐cadherin levels. Overall, our findings supported the conclusion that miR‐424‐5p promoter methylation reduced miR‐424‐5p expression and upregulated KIF2A, thereby promoting HCC EMT.